2008
DOI: 10.1111/j.1740-8261.2008.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contrast Media Formulation on Computed Tomography Angiographic Contrast Enhancement

Abstract: The characteristics of contrast media formulation (mgI/ml, osmolarity, and viscosity) are generally not considered important in computed tomography (CT) angiography in animals. The purpose of this study was to assess the contrast effect in CT angiography as a function of contrast media formulation, with a constant iodine dose. The contrast effects of three contrast media with different iodine concentrations were compared by administering identical iodine dosages (mgI/kg). The contrast effects of the three cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…dosage and route of injection of the contrast medium, as well as blood pressure and recumbency of the patient) which may limit the availability and distribution of the i.v. iodinated contrast administered in horses (Kishimoto et al . 2008; Pollard et al .…”
Section: Discussionmentioning
confidence: 99%
“…dosage and route of injection of the contrast medium, as well as blood pressure and recumbency of the patient) which may limit the availability and distribution of the i.v. iodinated contrast administered in horses (Kishimoto et al . 2008; Pollard et al .…”
Section: Discussionmentioning
confidence: 99%
“…11 In veterinary medicine, a few CT protocols have been evaluated for contrast enhancement of the caudal vena cava, abdominal aorta, and pulmonary artery. 8,10 However, to the authors' knowledge, a protocol for performing cardiac CT angiography has not been reported for veterinary species. A method is needed to help discriminate intraand extracardiac structures in dogs better than is achieved with echocardiography.…”
Section: Humentioning
confidence: 96%
“…This profile reflects the rapid distribution of contrast medium away from the cardiovascular system. 10 Consequently, nonuniform cardiovascular enhancement occurs during image acquisition when a uniphasic injection protocol is used. 10 A modified version of the uniphasic injection protocol, the multiphasic approach, includes flushing with saline (0.9% NaCl) solution or diluted contrast…”
Section: Conclusion and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Coronary angiography has classically been performed with X-ray imaging after contrast injection, and clinical methods can be used in large animals. Coronary imaging may also be done with computed-tomography (CT) angiography [34] as well as magnetic resonance angiography [35]. This may also be possible in small mammals, using microCT [36] and small bore, high magnetic field MR scanners [37], but these methods are still being developed.…”
Section: Hemodynamicsmentioning
confidence: 99%